تقرير أهداف التنمية المستدامة 2023: طبعة خاصة - United Nations Department of Economic; Social Affairs (United Nations, 2023)
The Sustainable Development Goals Report 2023: Special Edition provides a powerful call to action, presenting a candid assessment of the SDGs based on the latest data and estimates. While highlighting the existing gaps and urging the world to redouble its efforts, the report also emphasizes the immense potential for success through strong political will and the utilization of available technologies, resources, and knowledge. Together, the global community can reignite progress towards achieving the SDGs and create a brighter future for all. According to the report, the impacts of the climate crisis, the war in Ukraine, a weak global economy, and the lingering effects of the COVID-19 pandemic have revealed weaknesses and hindered progress towards the Goals. The report further warns that while lack of progress is universal, it is the world’s poorest and most vulnerable who are experiencing the worst effects of these unprecedented global challenges. It also points out areas that need urgent action to rescue the SDGs and deliver meaningful progress for people and the planet by 2030.